Political communication in a high-choice media environment: a challenge for democracy?. Issue 1 (2nd January 2017) - Van Aelst, Peter; Strömbäck, Jesper; Aalberg, Toril; Esser, Frank; de Vreese, Claes; Matthes, Jörg; Hopmann, David; Salgado, Susana; Hubé, Nicolas; Stępińska, Agnieszka; Papathanassopoulos, Stylianos; Berganza, Rosa; et al.
ABSTRACT: During the last decennia media environments and political communication systems have changed fundamentally. These changes have major ramifications for the political information environments and the extent to which they aid people in becoming informed citizens. Against this background, the purpose of this article is to review research on key changes and trends in political information environments and assess their democratic implications. We will focus on advanced postindustrial democracies and six concerns that are all closely linked to the dissemination and acquisition of political knowledge: (1) declining supply of political information, (2) declining quality of news, (3) increasing media concentration and declining diversity of news, (4) increasing fragmentation and polarization, (5) increasing relativism and (6) increasing inequality in political knowledge.